Clinicopathological correlation of odontogenic cysts and tumours in a South Indian population over a 20-year period - K C, Niranjan; Shaikh, Zulfin (International Journal of Dental Research, 2014)
Of several studies carried out worldwide, there is limited data available on the combined prevalence of odontogenic cysts and tumours in the Indian sub-continent. This study was designed to determine the prevalence of these lesions in the region of North Karnataka, South India over a period of 20 years. Histologically diagnosed cases of odontogenic cysts and tumours were reviewed from January 1989 to December 2008 and analyzed for age, gender and anatomical location and subjected to one way ANOVA and post Hoc statistical tests. 10.3% were odontogenic cysts and 2.13% were odontogenic tumours. Radicular cyst (50.8%) was the most common odontogenic cyst. Odontogenic cysts were frequent in males (63%) and anterior region of maxilla (54.4%) with a mean age of 27.8 years. The most common odontogenic tumour was Ameloblastoma (54.8%). Odontogenic tumours showed predilection for females (51%) and posterior region of mandible (68.4%) with a mean age for 29.9 years. Demographic profile of these lesions shows a distinct geographic variation. Keywords: Demographic profile, geographic variation, North Karnataka, odontogenic cysts, odontogenic tumours.